Turbomachinery rotordynamics phenomena modeling, and analysis - Childs, Dara (John Wiley New York, 1993)
Imparts the theory and analysis regarding the dynamics of rotating machinery in order to design such rotating devices as turbines, jet engines, pumps, and power transmission shafts. Takes into account the forces acting upon machine structures, bearings, and related components.
Includes Index.
Keywords: Turbomachines -- Dynamics; Impellers -- Dynamics; Rotors -- Dynamics